ENHANCING ENGLISH COMMUNICATION SKILLS FOR COMMUNITY EMPOWERMENT IN MULYAHARJA TOURISM VILLAGE - Resmayasari, Ira; Barus, Irma Rasita Gloria; Marithasari, Harries; Widodo, Gatot; Muttaqin, Ilham Arief (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study examined the enhancement of English communication skills among adults working in Mulyaharja’s Tourism Village, with the aim of empowering the community through improved language proficiency. Adopting Beeton’s Active Community Tourism Development Model, which emphasizes empowering local communities through active participation, the study involved 18 adult participants and four English instructors from the College of Vocational Studies of IPB University. Using a combination of questionnaires and a pre-test/post-test design, the research assessed participants’ language skills and perceptions before and after the training. The findings revealed a significant improvement in post-test scores, with an average increase of 50%, indicating the program’s effectiveness in fostering language skills. Participants reported high satisfaction rates, with 82% recognizing the relevance of the training to their professional and personal lives. These outcomes underscore the role of English proficiency in enhancing interactions with foreign tourists and supporting community development. Feedback also highlighted high motivation levels, as participants valued the training’s applicability to their roles, while observational notes captured challenges faced, offering insights into areas for future training improvements. The research highlights the potential of targeted English training in rural tourism contexts to strengthen community empowerment and communication skills, suggesting that future programs could benefit from extended courses and follow-up sessions to consolidate learning.